Creating Carmen Miranda : Race, Camp, and Transnational Stardom - Bishop-Sanchez, Kathryn (Book collections on Project MUSE., 2016)
""Creating Carmen Miranda analyzes the iconic figure of Carmen Miranda from its Brazilian origins to the present day and discusses how this image became emblematic of Latin America. It traces Miranda's stardom from the popular casino scene in Rio to the Broadway stage in the late 1930s, and on to Hollywood"--Provided by publisher"--